55th anniversary of the department of higher mathematics and mathematical physics of the physics faculty of BSU - Rusak, Valentin N.; Abrashina-Zhadaeva, Natalia G. (Journal of the Belarusian State University. Physics, 2017)
In this paper the attention is given to the main achievements of the department of higher mathematics and mathematical physics of the physics faculty in BSU for a period of 55 years of its existence. The main stages of the development of the department of higher mathematics and mathematical physics are listed below, beginning from the year 1961, when the department was founded as the department of general education for students of all specializations at the physics and the radio-physics and computer technologies faculties, providing numerous lecture courses and practical exercises in all sections of higher mathematics, and finishing with the becoming one of the leading departments of these faculties. The priority of the department is specified: it is largely associated with the transition to a 4-year education and conditioned with an average educational level of the entrants to the faculty of physics. It is also stated, that in addition to the research work, the department focuses on the development of the new approaches of teaching mathematics and, as a consequence, on the preparation of new teaching materials, series of training manuals on studied disciplines, on the search for new forms of organization of educational process, examinations and tests, organization and promotion of the independent work of students.